2021
DOI: 10.1039/d0fo02240c
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the antiaging effects of cereal- and food oil-derived active substances by a Caenorhabditis elegans model

Abstract: Cereal grains and oils contain various functional ingredients, such as amino acids, peptides, polyphenols, dietary fiber, linoleic acid, and natural pigments. Their biological activities are of great significance. Benefiting from...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…The administered dose of 50 μL promoted the reproductive capacity of C. elegans , while the other trials had the opposite results. It is reported that the reproductive capacity was related to the DAF-16/FoxO, which could be decreased by ACNs [ 15 ]. Compared with control, the spawning numbers in the 75, 100, 150, and 300 μL trials decreased by 24.9%, 28.7%, 46.6%, and 74.5%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The administered dose of 50 μL promoted the reproductive capacity of C. elegans , while the other trials had the opposite results. It is reported that the reproductive capacity was related to the DAF-16/FoxO, which could be decreased by ACNs [ 15 ]. Compared with control, the spawning numbers in the 75, 100, 150, and 300 μL trials decreased by 24.9%, 28.7%, 46.6%, and 74.5%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, Caenorhabditis elegans is a well-established model in genetics, which has been fully sequenced and is widely utilized in aging-related studies due to its short life cycle, rapid reproduction rate, and clear life extension mechanism [ 2 , 5 , 6 ]. It has been reported that some natural products have been shown to increase the lifespan of C. elegans , such as flavonoids [ 7 , 8 , 9 , 10 ], saponins [ 11 , 12 ], polysaccharides [ 13 , 14 ], cereal, and food-derived oil [ 15 ]. Anthocyanins (ACNs), a class of plant secondary metabolites, are natural pigments in plants which are stable in acid conditions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…AAs are important functional nutrients in cereal grains and are indispensable molecules in many biochemical synthesis pathways [31]. AAs are fundamental constituents of proteins and are precursors of other secondary metabolites [32].…”
Section: Introductionmentioning
confidence: 99%
“…Although in vitro models are useful as preliminary studies to evaluate bioactive potential, in vivo studies are required to further prove the bioactive effects of food derived compounds. Unfortunately, many of the typically used in vivo models are costly, time consuming, and can have complicated genetics ( Upadhyay and Palmberg, 2018 ; Xu et al, 2021 ). For this reason, researchers are looking at alternative in vivo models, such as Caenorhabditis elegans , to be a more practical model for studying the effects of food derived bioactive compounds in vivo .…”
Section: Introductionmentioning
confidence: 99%